PROGRAM PEMBERDAYAAN EKONOMI DESA DI DESA SLAMET KECAMATAN TUMPANG KABUPATEN MALANG - Fathur Rahman; Irma Fitriana Ulfah; Lukman Hakim (Publisher UPT P2M Politeknik Negeri Malang, 2019)
The problem faced by Slamet Village, Tumpang District, Malang Regency is the dependence of village finance on the Central Government. Slamet village does not have PADes, so village finance depends on government assistance and tax revenue sharing. Therefore, one of the village economic empowerments through the establishment of BUMDES is the first step to empowering the village economy in order to obtain PADes. This community service activity was carried out to provide initiation of the establishment of BUMDES in Slamet Village. This activity was attended by all village officials and representatives of several community organizations. The results of this service provide recommendations to map the potential that exists in Slamet Village and provide input to immediately compile the Village Regulation on the establishment of BUMDES. The compilation of this Perdes was the first step in establishing the BUMDES. Without the Perdes, the stages of establishing a BUMDES in improving the empowerment of the village economy cannot be realized.